2010
DOI: 10.1109/tac.2010.2042008
|View full text |Cite
|
Sign up to set email alerts
|

Supervisory Control for Opacity

Abstract: Abstract:In the field of computer security, a problem that received little attention so far is the enforcement of confidentiality properties by supervisory control. Given a critical system G that may leak confidential information, the problem consists in designing a controller C, possibly disabling occurrences of a fixed subset of events of G, so that the closed-loop system G/C does not leak confidential information. We consider this problem in the case where G is a finite transition system with set of events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(77 citation statements)
references
References 25 publications
0
76
0
1
Order By: Relevance
“…They provide sufficient conditions to compute an optimal controller preserving all secrets assuming that the controller has complete knowledge of the system and full control on it. In [10,12], the authors consider a control problem under partial observation and provide algorithms to compute the optimal controller ensuring the opacity of one secret against one attacker. Other works on the enforcement of opacity by means of controllers can be found in [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They provide sufficient conditions to compute an optimal controller preserving all secrets assuming that the controller has complete knowledge of the system and full control on it. In [10,12], the authors consider a control problem under partial observation and provide algorithms to compute the optimal controller ensuring the opacity of one secret against one attacker. Other works on the enforcement of opacity by means of controllers can be found in [25].…”
Section: Introductionmentioning
confidence: 99%
“…In [12], ensuring opacity is done by restricting the behaviors to an opaque subset. We investigate here another strategy which does not alter the system.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in [5], it was shown that there exists a maximally permissive and regular controller K † in all cases where Σ c ⊆ Σ o and Σ a compares with Σ c and Σ o . In [6], more elaborate constructions were presented for computing K † in the case where…”
Section: (B) the Secret Is Now Opaque With Respect To This Lts The mentioning
confidence: 99%
“…Note that [5] and [6] provide effective synthesis algorithms solving the opacity control problem (i.e., they compute the maximally permissive controller K † ), whereas [21] provides closed formulae characterizing the behavior K † /G without explicitly computing K † .…”
Section: (B) the Secret Is Now Opaque With Respect To This Lts The mentioning
confidence: 99%
See 1 more Smart Citation